PARTICLES, NEUTRINO AND PHOTONS IN THE MAGNETOSPHERE OF A COLLAPSING STAR - Kryvdyk, V. G. (Одеські астрономічні публікації, 2014)
The formation of the stellar magnetosphere during the gravitational collapse is discussed. Primary protons and electrons accelerate in the star’s magnetosphere during its gravitational collapse. In what follows, the flux of particles, photons and neutrinos generated in the magnetosphere is multiplied in a cascade process initiated by the self-interaction of particles and their interaction with magnetic fields. These processes are especially effective for the formation of magnetospheres in collapsing stars